Smoking and subsequent HPV infection: a mediation analysis - Eldridge, Ronald C. (Ann Epidemiol, 2017)
PURPOSE: Smoking is an established risk factor for a human papillomavirus (HPV) infection advancing to cervical precancer and cancer, but its role earlier in the natural history is less clear. Smoking is inversely associated with possessing HPV antibodies from a past infection suggesting that smoking may influence acquiring subsequent infections. METHODS: In a cohort of 1,976 U.S. women, we evaluate whether reduced antibodies to HPV-16 is a mechanism for smoking's role on acquiring a subsequent HPV-16 infection, through the analytic technique of causal mediation analysis. We posit a causal model and estimate two counterfactually-defined effects: a smoking impaired antibody-mediated indirect effect, and a non-mediated direct effect representing all other potential mechanisms of smoking. RESULTS: Compared to never smokers, current smokers had increased odds of HPV-16 infection by the antibody-mediated indirect effect (odds ratio=1.29, 95% confidence interval: 1.11, 1.73); the estimated direct effect was very imprecise (OR=0.57, 95% CI: 0.26, 1.13). We observed a stronger estimated indirect effect among women who smoked at least half a pack of cigarettes daily (OR=1.61, 95% CI: 1.27, 2.15) than among women who smoked less than that threshold (OR = 1.09; 95% CI: 0.94, 1.44). CONCLUSIONS: This is the first study to directly test the mechanism underlying smoking as an HPV cofactor. The results support current smoking as a risk factor earlier in the natural history of HPV, and are consistent with the hypothesis that smoking increases the risk of a subsequent infection by reducing immunity.